The last of the Mohicans (Leatherstocking tales, 2, 1, 1919)
"James Fenimore Cooper's romantic adventure brings the wilds of the American frontier and the drama of the French-Indian War vividly to life. The most popular of Cooper's Leatherstocking Tales, The Last of the Mohicans portrays the inevitable conflict of opposed cultures and stands as a testament to the ways in which this struggle has been mythologized. Featuring the well-loved noble woodsman Natty Bumppo, or "Hawk-eye," Cooper's novel is a memorable depiction of courage and passion, and a precursor to the Western genre."--BOOK JACKET.
The world of James Fenimore Cooper and The last of the Mohicans , Introduction by Stephen Railton , Cooper's introduction , The last of the Mohicans , Endnotes , Inspired by The last of the Mohicans , Comments & questions , For further reading.

Great expectations (The Oxford illustrated Dickens, ,, 2012)
Great Expectations is Charles Dickens's thirteenth novel. It is his second novel, after David Copperfield, to be fully narrated in the first person. Great Expectations is a bildungsroman, or a coming-of-age novel, and it is a classic work of Victorian literature. It depicts the growth and personal development of an orphan named Pip. The novel was first published in serial form in Dickens's weekly periodical All the Year Round, from 1 December 1860 to August 1861. In October 1861, Chapman and Hall published the novel in three volumes. Dickens originally intended Great Expectations to be twice as long, but constraints imposed by the management of All the Year Round limited the novel's length. The novel is collected and dense, with a conciseness unusual for Dickens. According to G. K. Chesterton, Dickens penned Great Expectations in "the afternoon of [his] life and fame." It was the penultimate novel Dickens completed, preceding Our Mutual Friend. It is set among the marshes of Kent and in London in the early to mid-1800s. The novel contains some of Dickens most memorable scenes, including its opening, in a graveyard, when the young orphan Pip is accosted by the escaped convict, Abel Magwitch. Great Expectations is a graphic book, full of extreme imagery, poverty, prison ships ("the hulks"), barriers and chains, and fights to the death. Upon its release, Thomas Carlyle spoke of "All that Pip's nonsense." Later, George Bernard Shaw praised the novel as "All of one piece and consistently truthfull." Dickens felt Great Expectations was his best work, calling it "a very fine idea," and was very sensitive to compliments from his friends: "Bulwer, who has been, as I think you know, extraordinarily taken by the book." Great Expectations has a colourful cast that has entered popular culture: the capricious Miss Havisham, the cold and beautiful Estella, Joe the kind and generous blacksmith, the dry and sycophantic Uncle Pumblechook, Mr. Jaggers, Wemmick with his dual personality, and the eloquent and wise friend, Herbert Pocket. Throughout the narrative, typical Dickensian themes emerge: wealth and poverty, love and rejection, and the eventual triumph of good over evil. Great Expectations has become very popular and is now taught as a classic in many English classes. It has been translated into many languages and adapted many times in film and other media.
by Charles Dickens

The adventures of Tom Sawyer (The Mark Twain in Person Audio Library, ,, 2012)
"Mark Twain's classic The Adventures of Tom Sawyer has been enjoyed by generations of readers across the world since its publication in 1876. With its humorous glimpses into life in nineteenth-century, small-town America, this novel has provided unique social commentary that continues to be discussed in classrooms today. Tom Sawyer, a mischievous boy growing up in the fictional town of St. Petersburg, Missouri, is constantly getting in and out of trouble with his friend Huckleberry Finn. Based on Twain's own childhood, this novel not only gives profound insights into American life but also shows how children can develop moral codes based on friendship, loyalty, and respect"--
15 copies of the audiobook.

Treasure Island (A Signet classic CE1610, ,, 1975)
"Young Jim Hawkins and his friends set sail for Treasure Island, hoping to find the buried loot of Captin Flint, fiercest of all the pirates. But, unknown to them, the crew of their own ship is made up of Flint's former crew, led by the evil one-legged pirate Long John Silver. Once on the island Jim and his friends must find the buried treasure and escape before the pirates capture them. Robert Louis Stevenson's timeless tale of greed and gold remains the most exciting adventure story ever written."--P. [4] of cover.
Old buccaneer , Sea cook , My shore adventure , Stockade , My sea adventure , Captain Silver , Questions, questions, questions / Arthur Pober , About the author, about the illustrator.

David Copperfield (Oxford world's classics, ,, 2012)
Growing Up! Young David Copperfield, orphaned as a child, abandoned by a vicious stepfather, must learn to make a life for himself. In Charles Dickens' brilliant novel, we learn of David's early harsh years... his adoption by his eccentric aunt... his betrayal by a childhood friend... the pressures of starting a career... immature, young love... and finally career success and personal happiness. Charles Dickens' sensitive portrayal of David's early years has made David Copperfield one of the world's most beloved novels.
David Copperfield , Appendix I: Extracts from John Forster's Life of Dickens , Appendix II: The number-plans for David Copperfield , Appendix III: The draft titles.

The tale of Peter Rabbit (Mackin classics, ,, 2012)
Share Peter Rabbit's many adventures in Mr. McGregor's garden. Peter narrowly excapes fromt he garden without his clothes, but with a tummy-ache--only to be treated with the dreaded camomile tea at home.

The Jungle Book (Mackin classics, ,, 2012)
Imagine growing up among wolves, being friends with a panther and a bear, and hunting the most fearsome animal in the wild-the man-killing tiger Shere Khan. These are the stories of Mowgli ""the frog,"" a man-cub raised by wolves, and his journey to adulthood with the help of Baloo the bear, and Bagheera the black panther. The Jungle Book is collections of short stories. Each story begins with a few lines of poetry. The best known of these jungle stories involve the adventures of Mowgli the jungle boy raised by wolves, and his friends Baloo the bear, and Bagheera the black panther. With deep truths and deep insights into and from the human and animal perspective Rudyard Kipling's The Jungle Book remain a priceless treasure to all.
Mowgli's brothers , Hunting-song of the Seeonee pack , Kaa's hunting , Road-song of the bandar-log , "Tiger! Tiger!" , The white seal , Mowgli's song , Lukannon , "Rikki-tikki-tavi" , Darzee's chaunt , Toomai of the elephants , Shiv and the grasshopper , Her majesty's servants , Parade-song of the camp animals.

A Christmas Carol (Puffin chalk, ,, 2012)
"When A Christmas Carol was first published in 1843 it was an overnight success, and set a precedent that was to be followed by other Christmas books, including The Chimes (1844) and The Cricket (1845). Each book was published at the same time of year, in the same format, and extolled similar values about the virtues of love, charity and the family unit. But none would achieve the cult status of A Christmas Carol, a book so popular it has become part of the landscape of the traditional Christmas, or produce a character as extraordinarily memorable. A celebration of Christmas, a tale of redemption and a critique on Victorian society, Dickens atmospheric novella follows the miserly, penny-pinching Ebenezer Scrooge who views Christmas as 'humbug. It is only through a series of eerie, life-changing visits from the ghost of his deceased business partner Marley and the spirits of Christmas past, present and future that he begins to see the error of his ways. With heart-rending characters, rich imagery and evocative language, the message of A Christmas Carol remains as significant today as when it was first published"--
Marley's ghost , First of the three spirits , Second of the three spirits , Last of the spirits , End of it.

Little women (Little Women series, 1, 1, 2012)
For generations, children around the world have come of age with Louisa May Alcott's March girls: hardworking eldest sister Meg, headstrong, impulsive Jo, timid Beth, and precocious Amy. With their father away at war, and their loving mother Marmee working to support the family, the four sisters have to rely on one another for support as they endure the hardships of wartime and poverty. We witness the sisters growing up and figuring out what role each wants to play in the world, and, along the way, join them on countless unforgettable adventures. Readers young and old will fall in love with this beloved classic, at once a lively portrait of nineteenth-century family life and a feminist novel about young women defying society's expectations.
Four sisters , A merry Christmas , The Laurence boy , Being neighborly , Jo and her temper , Meg tries to be fashionable , Summer and dreams , Secrets , A telegram , Dark days , Serious conversations , Aunt March settles the question , The first wedding , Endeavors , Domestic experiences , Calls , Jo's friend , Heartache , Beth's secret , Lazy Laurence , The Valley of the Shadow , Learning to forget , All alone , Under the umbrella.

The Wizard of Oz (Oz books, , 1, 2011)
Join Dorothy Gale, Toto, and all of her friends as they explore the incredible land of Oz. The Wonderful Wizard of Oz is American's most enduring fairy tale. From the moment Dorothy puts on the silver slippers (changed to ruby slippers by MGM to take advantage of their new advance in movie making: color) until the moment she clicks her heals and returns home to Kansas you will be swept away and captivated by her extraordinary story. This lavishing illustrated edition has more than one hundred and fifty of the original W. W. Denslow illustrations.
The cyclone , The council with the munchkins , How Dorothy saved the scarecrow , The road through the forest , The rescue of the tin woodman , The cowardly lion , The journey to the great oz , The deadly poppy field , The queen of the field mice , The guardian of the gates , The wonderful emarld city of oz , The search for the wicked witch , The rescue , The winged monkeys , The discovery of Oz, the terrible , The magic art of the great humbug , How the balloon was launched , Away to the south , Attacked by the fighting trees , The dainty China country , The lion becomes the king of the beasts , The country of the quadlings , Glinda grants Dorothy's wish , Home again.

The call of the wild (Mackin classics, ,, 2012)
Stolen From Home and sold into a harsh life as a sled dog in northern Canada, Buck must quickly learn to survive. He soon takes his place as leader of the hardworking team, and his strength and courage become legendary among men. But the call of the wild is strong, awakening primal feelings of a life among wolves... One of the greatest of all wildlife stories, The Call of the Wild will enthrall today's readers as it has since its first publication in 1903. With powerful engravings by artist Andrew Davidson and a compelling foreword by author and naturalist Jean Craighead George, this handsome new edition brings Jack London's classic tale vividly to life. Complete and unabridged, Kingfisher Classics are the ideal introduction for any child to some of the best-loved stories in literature.
Call of the wild --, To Build a Fire --, Love of Life --, To the Man on the Trail.

The hound of the Baskervilles (Sherlock Holmes mysteries, 5, 1, 2012)
At Baskerville Hall on the grim moors of Devonshire, a legendary curse has apparently claimed one more victim. Sir Charles Baskerville has been found dead. There are no signs of violence, but his face is hideously distorted with terror. Has the spectral destroyer struck again? More important, is Sir Henry Baskerville, younger heir to the estate, now in danger? Enter Sherlock Holmes, summoned to protect Sir Henry. As Holmes and Watson begin to investigate, a blood-chilling howl from the fog-shrouded edges of the great Grimpen Mire.
Mr. Sherlock Holmes , The curse of the Baskervilles , The problem , Sir Henry Baskerville , Three broken threads , Baskerville Hall , The Stapletons of Merripit House , First report of Dr. Watson , The light upon the Moor , Extract from the diary of Dr. Watson , The man on the Tor , Death on the moor , Fixing the nets , The Hound of the Baskervilles , A retrospection.

The story of a fierce bad rabbit (World of Beatrix Potter Peter Rabbit, ,, 1987)
The fierce bad rabbit takes away the nice gentle rabbit's carrot. But, a hunter with a gun takes the fierce bad rabbit's tail and whiskers

The Tale of the flopsy bunnies (Classic tales by Beatrix Potter, , 1, 1987)
When the Flopsy Bunnies venture over to Mr. McGregor's garbage heap to find dinner, trouble ensues when they fall asleep in the warm sun after their meal.

The tale of the pie and the patty pan (World of Beatrix Potter Peter Rabbit, ,, 1987)
A pussycat has a very unusual tea party for a little dog.

The wonderful wizard of Oz (The Wizard of Oz series, 1, 1, 2001)
After a cyclone transports her to the land of Oz, Dorothy must seek out the great Wizard in order to return to Kansas. This volume is a facsimile of the 1900 edition.
The cyclone , The council with the Munchkins , How Dorothy saved the scarecrow , The road through the forest , The rescue of the tin woodman , The cowardly lion , The journey to the Great Oz , The deadly poppy field , The queen of the field mice , The guardian of the gates , The wonderful emerald city of Oz , The search for the wicked witch , How the four were reunited , The winged monkeys , The discovery of Oz the terrible , The magic art of the great humbug , How the balloon was launched , Away to the south , Attacked by the fighting trees , The dainty china country , The lion becomes the king of beasts , The country of the Quadlings , The good witch grants Dorothy's wish , Home again.

Anne of Green Gables (Anne of Green Gables, 1, 1, 2012)
As soon as Anne Shirley arrived at the snug, white farmhouse called Green Gables, she knew she wanted to stay forever. But would the Cuthberts send her back to the orphanage? Anne knows she's not what they expected -- a skinny girl with decidedly red hair and a temper to match. If only she could convince them to let her stay, she'd try very hard not to keep rushing headlong into scrapes or blurt out the very first thing she had to say. Anne was not like anybody else, everyone at Green Gables agreed; she was special -- a girl with an enormous imagination. This orphan girl dreamed of the day when she could call herself Anne of Green Gables. Annotation. As soon as Anne Shirley arrived at the snug, white farmhouse called Green Gables, she knew she wanted to stay forever... but would the Cuthberts send her back to the orphanage? Anne knows she's not what they expected -- a skinny girl with decidedly red hair and a temper to match. If only she could convince them to let her stay, she'd try very hard not to keep rushing headlong into scrapes or blurt out the very first thing she had to say. Anne was not like anybody else, everyone at Green Gables agreed; she was special -- a girl with an enormous imagination. This orphan girl dreamed of the day when she could call herself Anne of Green Gables.
Mrs. Rachel Lynde is surprised , Matthew Cuthbert is surprised , Marilla Cuthbert is surprised , Morning at Green Gables , Anne's history , Marilla makes up her mind , Anne says her prayers , Anne's bringing-up is begun , Mrs. Rachel Lynde is properly horrified , Anne's apology , Anne's impressions of sunday-school , Solemn vow and promise , Delights of anticipation , Anne's confession , Tempest in the school teapot , Diana is invited to tea with tragic results , New interest in life , Anne to the rescue , Concert, a catastrophe, and a confession , Good imagination gone wrong , New departure in flavorings , Anne is invited out to tea , Anne comes to grief in an affair of honor , Miss Stacey and her pupils get up a concert , Matthew insists on puffed sleeves , Story club is formed , Vanity and vexation of spirit , An unfortunate lily maid , An epoch in Anne's life , Queen's class is organized , Where the brook and river meet , Pass list is out , Hotel concert , Queen's girl , Winter at Queen's , Glory and the dream , Reaper whose name is death , Bend in the road , Biography of L. M. Montgomery / Caroline Parry.

Gulliver's Travels (Oxford world's classics, ,, 2012)
The wayward traveler -- Lemuel Gulliver -- ends up on a series of bizarrely populated islands. First he is a giant among little people, but then sees the situation reversed when he's surrounded by giants twelve times his size. Next he finds himself in the clouds, in a society of devoted but ultimately hapless mathematicians. Lastly, his journey brings him to an island where incredibly noble horses must deal with a race of uncouth, reviled ape-men: the Yahoos.
The publisher to the reader , A letter from Captain Gulliver to his cousin Sympson , A voyage to Lilliput , A voyage to Brobdingnag , A voyage to Laputa, Balnibarbi, Luggnagg, Glubbdubdrib, and Japan , A voyage to the country of the Houyhnhnms.

Pollyanna (Pollyanna, 1,, 2001)
An abridged version of the tale of orphaned, eleven-year-old Pollyanna, who comes to live with austere and wealthy Aunt Polly, bringing happiness to her aunt and other members of the community through her philosophy of gladness. Pollyanna knows the secret to finding a smile -- even when really bad things happen. From the moment she arrives in Beldingsville, she shares her Glad Game with everyone around her. But the person who needs Pollyanna's help the most doesn't want it. - Publisher.

A tale of two cities (Oxford world's classics, ,, 2012)
It was the time of the French Revolution - a time of great change and great danger. It was a time when injustice was met by a lust for vengeance, and rarely was a distinction made between the innocent and the guilty. Against this tumultuous historical backdrop, Dickens' great story of unsurpassed adventure and courage unfolds.Unjustly imprisoned for 18 years in the Bastille, Dr. Alexandre Manette is reunited with his daughter, Lucie, and safely transported from France to England. It would seem that they could take up the threads of their lives in peace. As fate would have it though, the pair are summoned to the Old Bailey to testify against a young Frenchman - Charles Darnay - falsely accused of treason. Strangely enough, Darnay bears an uncanny resemblance to another man in the courtroom, the dissolute lawyer's clerk Sydney Carton. It is a coincidence that saves Darnay from certain doom more than once. Brilliantly plotted, the novel is rich in drama, romance, and heroics that culminate in a daring prison escape in the shadow of the guillotine.
Mysterious message , Recalled to life , Shoemaker , Trial of Charles Darnay , Moment of terror , Marquis St. Evremonde , Sidney's confession , Grave robbers , Spies , Sound medical advice , Revolution erupts , Dangerous journey , Dr Manette's new power , Spy is unmasked , Doomed! , Fateful meeting , Fleeing the revolution , Outwitting the guillotine.